Determination of ethanol in wines by flow injection spectrophotometry using gas-diffusion and an immobilized enzyme reactor - Rangel, António O. S. S. (2011)
A flow injection analysis (FIA) system for the spectrophotometric determination of ethanol in wines using an immobilized alcohol dehydrogenase reactor was developed. A gas diffusion unit was used to achieve a large dilution and to separate ethanol from the matrix. This way, the contact of the sample with the reactor was avoided and possible interferences in the spectrophotometric measurements were significantly reduced. The alcohol dehydrogenase enzyme was immobilized on alkylaminated controlled pore glass, and the consumption of the NAD cofactor was minimized (0.6 µmol per assay) by using the merging zone technique. The detection limit was 0.4% (v/v). Good precision was achieved, with relative standard deviations less than 2.2% (n = 9). For 20 samples of different types of table and Port wines, the results showed good agreement with the OIV usual procedure, the relative deviation being less than 4.4%. Thirty determinations per hour can be carried out within the ethanol concentration range of 5% to 25% (v/v), without any sample pretreatment.